Amputation history and rehabilitation of black men living in the greater Durban area who have had traumatic amputations of the lower limb - B. A. Kubheka; L. R. Uys (AOSIS, 1995)
A survey was undertaken amongst twenty five black men living in the greater Durban area who had had amputations of the lower limbs. The type of amputation care and the rehabilitation programme they underwent post-operatively is described. The sample included men from 24 to 50 years of age, of whom the majority were from rural areas. The amputation care intra and post-operatively was marked by the lack of emotional preparation pre-operatively, and lack of rehabilitation information and teaching afterwards. Most respondents had to find information for themselves. This lack of information and teaching seemed to impede physical rehabilitation, with stump sores and limited use of prostheses being the main problems. Vocational rehabilitation was almost totally absent. In contrast to the twenty two respondents who worked before their amputations, only four worked afterwards. The majority had to support their families alone; sixteen of them were totally reliant on a Disability Grant. These problems lead to social isolation, depression, loneliness and other psycho-social problems.